Survei Minat Pembelajaran PJOK Siswa Kelas VII SMP Negeri 08 Palembang - Saputra, Ahmad Muchlis; Destriani, Destriani; Yusfi, Herri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the learning interest of class VII students in participating in PJOK learning at SMP Negeri 08 Palembang for the 2023/2024 academic year. This research is descriptive. The method used is a survey with data collection techniques using Google Forms. The subjects in this research were all class VII students at SMP Negeri 08 Palembang for the 2023/2024 academic year, totaling 133 students. The data analysis technique uses quantitative descriptive analysis expressed in percentage form. The overall results of this research show that 133 students are in the medium category. With details in the categories "Very High" totaling 8 students (6%), "High" 35 students (26%), "Medium" 45 students (34%), "Low" 36 students (27%), and "very low" 9 students (7). Based on the average value, namely 60.9% of class VII students' interest in participating in PJOK learning at SMP Negeri 08 Palembang for the 2023/2024 academic year in the "Medium" category. It can be concluded that the interest of class VII students in participating in PJOK learning at SMP Negeri 08 Palembang for the 2023/2024 academic year is in the medium category. Keywords: Interest, PJOK Learning, SMP Negeri 08 Palembang